Analisis Risiko Usahatani Hidroponik (Studi Kasus: Kisma Lestari Farm, Karangpandan) - Hanif, Muhammad Gustika; Heryanto, Mahra Arari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Kisma Lestari Farm is an agricultural enterprise focused on the production of leafy vegetables in Karanganyar Regency, facing various risks that may hinder supply continuity and the fulfillment of market demand. Field observations indicate that the seedling failure rate reaches 25–30%, accompanied by crop damage caused by pests and diseases from the early nursery stage. This study aims to analyze the hydroponic vegetable supply chain, identify risks in the production process, and formulate mitigation strategies applicable to Kisma Lestari Farm. The research method employed is qualitative with a case study approach, utilizing the House of Risk (HOR) analysis to assess risks and develop mitigation actions. The results show that there are five stages of hydroponic vegetable production, with the identification of 23 risk events and 10 risk agents, including five priority risk agents that require immediate attention. Furthermore, 15 mitigation actions were proposed, with five key actions considered the most effective, namely providing a daily checklist for cultivation process control, implementing and complying with Standard Operating Procedures (SOPs), enhancing workers’ knowledge of hydroponic cultivation and maintenance techniques, as well as scheduling planting times based on forecasted environmental conditions..